2008
DOI: 10.1002/path.2483
|View full text |Cite
|
Sign up to set email alerts
|

An integrated proteomics approach for studying the molecular pathogenesis of Dupuytren's disease

Abstract: Dupuytren's disease (DD) is a fibromatosis characterized by non-malignant transformation of palmar fascia leading to permanent contraction of one or more fingers. Despite the extensive knowledge of its clinical pathogenesis, the aetiology of this disease remains obscure. In the present paper, we report for the first time on the proteomic profiling of diseased versus unaffected patient-matched palmar fasciae tissues from DD patients using two-dimensional gel electrophoresis coupled with mass spectrometry analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Two whole-proteome studies have been carried out to identify differentially expressed proteins in DD 21 22. While O'Gorman et al 22 identified three potential low molecular weight tissue protein markers that were positively associated with DD, the genes coding for these protein markers were not determined; therefore these findings were not included in this review.…”
Section: Comparing Global Rna Expression With Protein Expressionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two whole-proteome studies have been carried out to identify differentially expressed proteins in DD 21 22. While O'Gorman et al 22 identified three potential low molecular weight tissue protein markers that were positively associated with DD, the genes coding for these protein markers were not determined; therefore these findings were not included in this review.…”
Section: Comparing Global Rna Expression With Protein Expressionmentioning
confidence: 99%
“…While O'Gorman et al 22 identified three potential low molecular weight tissue protein markers that were positively associated with DD, the genes coding for these protein markers were not determined; therefore these findings were not included in this review. By comparing biopsies of DD with internal palmar fascia, Kraljevic Pavelic et al 21 have reported 44 genes showing five-fold upregulation in DD through two-dimensional gel electrophoresis. Of these genes, three were reported in mRNA expression profiling microarrays with consistent regulation; ARHGDIA ,8 COL6A3 (meta-analysis) and TPM4 11 .…”
Section: Comparing Global Rna Expression With Protein Expressionmentioning
confidence: 99%
See 3 more Smart Citations